Effect of quenching temperature on the structure and properties of Cu-Zr-Al glassy ribbons - Lu Cao; Hao-Ran Jiang; Jochi Tseng; Yi-Fan Gao; Qing Wang; Yan-Dong Jia; Lina Hu; Gang Wang (Journal of Materials Research and Technology)
Since the glass structure is inherited from the alloy melt, the thermal history experienced by the melt during cooling significantly influences the structure and properties of metallic glasses. In this work, the effect of melt quenching temperature on the atomic structure, thermophysical properties, and mechanical properties of a Cu-Zr-Al metallic glass is systematically investigated, using a combination of state-of-the-art techniques, including synchrotron-based high-energy X-ray diffraction and chip-based flash differential scanning calorimetry. It is found that for the studied Cu-Zr-Al alloy, the temperature window for preparing completely amorphous and contamination-free ribbons is remarkably narrow, spanning merely ∼150 K. This window is bounded by heterogeneous nucleation due to the unmelted nuclei at the lower limit and significantly increased O content due to severe chemical reactions at the higher limit. Furthermore, the glass transition, crystallization, thermal stability, and mechanical properties of the Cu-Zr-Al alloy are found to be highly sensitive to the melt temperature prior to quenching during melt-spinning. Two key factors—the disordering and homogenization effects—as well as the progressive enhancement of O contamination with increasing quenching temperature—are revealed to govern the structural and property evolutions. These findings provide valuable insights into tailoring glass structures and properties through the deliberate control of melt thermal history.